Speaking Task Instruction in English Textbook: Bahasa Inggris for Grade X - Melati Theresia; Dian Mega Putri; Riny Dwitya Sani (AL-ISHLAH: Jurnal Pendidikan, 2022)
This article aims to analyse the task instruction of speaking tasks in an English student’s book for grade X that Balitbang Kemdikbud publishes. As the first edition of the textbook, some inaccuracies might be found especially related to task instruction. This is descriptive research with checklist evaluation as the instrument of the research. The checklist evaluation of task instruction consists of six sub-indicators. Four evaluators, the English teachers who use the book, fulfilled the checklist evaluation. Based on the findings, six chapters of the book have salience task instruction, seven chapters have succinct task instructions, eight chapters have sufficient task instruction, seven chapters in the book have standardised task instruction, and all chapters in the book have the sequence in the task instruction, and also the task instruction in the textbook has a clear target of the task. In short, the task instruction of speaking task already fulfils the criteria of good task instruction. However, several criteria need to be revised.